Essential Quantitative Methods / For Business, Management and Finance - Oakshott Les; Macmillan Business (1998)
This book covers the major topics likely to be taught on a quantitative method course and is written in a concise but student-friendly style. Preface, Revision Mathematics, Index Numbers, Investment Appraisal, Sampling Methods, Presentation of Data, Summarizing Data, Probability and Decision-Making, The Normal Distribution, Analysis and Interpretation of Sample Data, Testing a Hypothesis, Correlation and Regression, Time Series Analysis, Linear Programming, Critical Path Analysis, Inventory Control, Simulation, Appendices, Index.